Education and Implementation of Waste Bank as a Circular Economy Solution at Ma’had Tafaqquh: Edukasi Dan Implementasi Bank Sampah Sebagai Solusi Ekonomi Sirkular Di Ma'had Tafaqquh - Martalasari; Sri Wahyuni; Asrori, Ikrima; Widayat, Prama; Sari, Ermina; Awal, Raudhah; Chahyadi , Ennie (Universitas Lancang Kuning, 2025)
Waste management is one of the major challenges in various institutions, including in the Ma'had Tafaqquh environment. Lack of awareness of waste in sorting and managing it causes the accumulation of organic and inorganic waste which has a negative impact on the environment. To overcome this problem, the concept of a circular economy through the Digital Waste Bank is present as an innovative solution that integrates environmental education and the use of technology. This program aims to increase awareness of waste management based on the 3R principle (Reduce, Reuse, Recycle) and encourage economic empowerment by utilizing waste that has a selling value. The activities carried out include education for students and residents of Ma'had Tafaqquh regarding waste management, training in the use of the Digital Waste Bank application, and implementation of an effective waste sorting system. The Digital Waste Bank allows for transparent waste recording and management as well as the provision of economic incentives. It is hoped that the results of this program will not only create a cleaner and healthier environment, but also build a sustainable culture and economic independence in Ma'had Tafaqquh.